PIMBA: A PIpeline for MetaBarcoding Analysis - Oliveira, Renato R. M.; Silva, Raíssa; Nunes, Gisele L.; Oliveira, Guilherme (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2021: Anais do XIV Simpósio Brasileiro de Bioinformática, 2021)
DNA metabarcoding is an emerging monitoring method capable of assessing biodiversity from environmental samples (eDNA). Advances in computational tools have been required due to the increase of Next-Generation Sequencing data. Tools for DNA metabarcoding analysis, such as MOTHUR, QIIME, Obitools, PEMA, and mBRAVE have been widely used in ecological studies, however, some difficulties are encountered when there is a need to use custom databases. Here we present PIMBA, a PIpeline for MetaBarcoding Analysis, which allows the use of customized databases, as well as other reference databases used by the software mentioned here. PIMBA is an open-source and user-friendly pipeline that consolidates all analyses in just three command lines. PIMBA’s implementation is available at https://github.com/reinator/pimba .